Designing a Conceptual Model for Internet Data Center - Sharmila Devi, Marimuthu (2003)
The purpose of this article is to describe the development of a conceptual model for Internet data center (IDC). IDC is a facility where many organizations can leverage a single, shared infrastructure to economically host Internet servers and services. The key architectural elements of the IDC network include clients, perimeter routers, load balancers, cloned front-end Web servers, multilayer switches, firewalls, infrastructure servers and back-end database and management systems. This paper focuses on the logical components that provide an infrastructure that is scalable, available, secure, and manageable. The major benefits of IDC are, it will reduce capital and operating expenses in an organization. Large businesses are models of dynamic change. They usually start small and grow exponentially with demand. They grow both in the number of unique users supported, which can grow extremely quickly, and in the complexity and integration of user services offered. This growth must be built on a solid architectural foundation that supports high availability, a secure infrastructure, and a management infrastructure.